Pembaruan Hukum Nasional dalam Menjawab Tantangan Globalisasi dan Digitalisasi - Rasyid Tarmizi; Irwan Triadi (Indonesian Journal Publisher, 2025)
The rapid development of globalization and digitalization has significantly influenced various aspects of human life, including national legal systems. These transformations demand that states undertake comprehensive and sustainable legal reforms to address emerging challenges such as personal data protection, cybercrime, digital economy regulation, and cross-border jurisdictional issues. This study aims to analyze the urgency of national legal reform in responding to the dynamics of globalization and digitalization, as well as to identify strategic steps for developing an adaptive, responsive, and equitable legal system. The research employs a normative juridical method through legal analysis of relevant national and international laws and regulations, complemented by a literature review of global frameworks and comparative legal studies. The results indicate that legal reform must be comprehensive, covering the dimensions of legal substance, institutional structure, and legal human resources. Furthermore, reform efforts should be guided by the principles of national legal sovereignty, human rights protection, and alignment with global technological developments and international legal standards. The study concludes that through the modernization of its legal system, Indonesia can enhance its global competitiveness, protect national interests, and promote social justice in the digital era. An updated, inclusive, and forward-looking legal framework will ensure Indonesia’s readiness to face transnational legal challenges arising from ongoing globalization and rapid digital transformation.